Digital Literacy Skills of University Students in English for Specific Purposes (ESP) Learning - Melvina, Melvina; Rosba, Evriliani; Sukaesih, Sri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
English has emerged as a global language, necessitating its mastery among students, particularly given the abundance of learning resources and information accessible online. As a result, digital literacy, defined as the ability to search for and utilize digital information effectively, has become an essential competency. This study aims to examine the digital literacy skills of university students in the context of learning English for specific purposes, namely biology. The investigation focuses on four dimensions of digital literacy: operational skills in using technological devices, critical thinking in digital contexts, digital collaboration abilities, and awareness regarding the appropriate use of digital technologies. Employing a quantitative research design, data were gathered through an online survey distributed to 134 biology students from four universities in Indonesia. The data were analyzed using descriptive statistical techniques. The findings revealed that the students’ average digital literacy score was 85.24, which falls within the “outstanding” category. These results highlight the pivotal role of digital literacy in enabling students to access information more effectively and enhance both their disciplinary knowledge and English language proficiency.